Determinants and preferences for a crowdfunding project - Mohammad Tariqul Islam Khan (Future Business Journal, 2022)
Abstract This paper aims to investigate what determines young working individuals’ willingness to fund a crowdfunding project, and their preferences for a crowdfunding model (e.g. debt-based crowdfunding or equity-based crowdfunding). Using a survey dataset (n = 297) from an emerging country where crowdfunding is gaining popularity, the results demonstrate that an easy investment process, which is viewed as perceived development and innovation of crowdfunding, and financial training cause young working individuals’ higher willingness to invest in a crowdfunding project, whereas perceived risk involved with a crowdfunding project reduces the willingness to fund a crowdfunding project. With regard to the preference for a crowdfunding model, the results show that managing a bank account is positively related to the likelihood of investment in debt-based crowdfunding model. The findings provide implications for crowdfunding investors, project founders, and policy makers.